Molecular study of selected Zingiberaceae species from ex situ collection of Peninsular Malaysia - Akram, Seemab (2021)
Zingiberaceae is the largest ginger family in the order Zingiberales and containing 55 genera and more or less 1300 species. This family comprises of several subfamilies and genus according to different taxonomical classifications which are classical taxonomy classification with one sub-family and four tribes whereas molecular taxonomy comprise of four sub-families and six tribes. Family Zingiberaceae is highly distributed in Malaysia with 20% taxa and 40% genera represented in the world. Benefits of this species can be used as traditional medicines and have antioxidant compounds such as flavonoids. Antioxidant compounds in Zingiberaceae have remarkable biological activities. However, there are still many biological aspects of this family that need to be studied including its taxonomy and antioxidant genes. The cryptic morphologies within the family have hindered accurate taxonomy classification using the conventional method. Therefore, more accurate taxonomy classification using the molecular method is required until the species level. Meanwhile, one of the important antioxidant genes which is the CHS gene is known as a conserved gene in plants. But not much information is available about this gene in Zingiberaceae except for several species such as Curcuma longa. Therefore, the main aim of this study was to improve biological data for selected Zingiberaceae species for better species assessment, management and conservation as well as scientifically justify the value of this species as an antioxidant source. Specifically, this study addressed the following objectives: (i) to screen out informative RAPD and ISSR markers for phylogeny tree construction of 20 selected Zingiberaceae species, (ii) to construct a phylogeny tree of 20 selected Zingiberaceae species, (iii) to perform in silico comparative analysis of CHS1 gene between Zingiberaceae, Costaceae and Poaceae, and (iv) to develop new CHS gene primers for four selected endemic Zingiberaceae species. In this study, a total of 20 selected species of Zingiberaceae were collected from the Agricultural Conservatory Park, Institute of Bioscience (IBS), Universiti Putra Malaysia (UPM). Sample of leaves were extracted using Qiagen DNeasy plant mini kit by following the manufacturer’s protocol with some modifications. All extracted DNA were screened for 11 RAPD and six ISSR primers and followed by genotyping. A dendrogram was constructed using the unweighted pair group method with arithmetic average (UPGMA) using NTSYS-PC 2.10e software. Meanwhile, sequences of the Chalcone synthase 1 (CHS1) gene belonging to the Commelinids clade (three families; Zingiberaceae, Costaceae and Poaceae) were retrieved from the GeneBank and checked for their similarity using BLASTn. In follow, in silico comparative analysis was performed. All sequences with 565 bp length were aligned using BioEdit 7.2 software and then, a Neighbour Joining tree was constructed using MEGA X. Later, CHS gene primers for four selected endemic Zingiberaceae species (Alpinia mutica, Etlingera venusta, Hornstedtia leonurus and Scaphochlayms kunstleri) were designed using Primer3 software, and in silico analyzed using Oligo analyzer. From this study, three dendrograms were constructed based on three RAPD markers, three ISSR markers and combined three RAPD and three ISSR markers. From those three dendrograms, a combined data of RAPD and ISSR phylogenetic tree provided a clear molecular taxonomic classification of 20 selected Zingiberaceae species and was comparable to previous conventional and molecular taxonomy trees. Thus, a combined data of RAPD and ISSR had addressing a clear phylogenetic classification of the 20 selected Zingiberaceae species. For in silico comparative analysis of the CHS1 gene study, three mutations were observed; substitution, insertion and deletion. A total of 103 potential SNPs were found and showed 18.23% polymorphism. Then unrooted NJ tree was constructed and formed two clades — with no clear divergence among the three studied families. This suggests that the CHS1 gene in the Commelinids clade is conserved with low polymorphism. The 12 pairs of new CHS genic primers for four selected endemic Zingiberaceae species were successfully designed and are expected to amplify at loci ranges from 266 bp to 2072 bp. In conclusion, this study has improved the current biological data of selected Zingiberaceae species which provide better species assessment, management and conservation as well as scientifically justifying the value of this economically important species as an antioxidant source. Further studies are still needed to look at the population diversity of each Zingiberaceae species so that the uniqueness of each population of each species can be well managed and preserved. Further studies are also needed to confirm those newly designed CHS genic primers can be used in the CHS omics studies of Zingiberaceae.